Retrospective Evaluation of Implementation of Long-Term Forecast on Spatial Spread of Rabies in the Asian Part of Russia - A. D. Botvinkin; G. N. Sidorov; E. M. Poleshchuk; L. D. Zarva; D. N. Nashatyreva; N. V. Yakovchits; E. I. Andaev; S. V. Balakhonov; N. V. Rudakov (Проблемы особо опасных инфекций, 2020)
Objective: To evaluate the historical long-term forecast of the spatial spread of rabies in Siberia and Far East and to characterize modern approaches to spatial forecasting. The concept of spatial spread of rabies in the Asian part of Russia, developed in the 80s of the twentieth century, is subjected to critical analysis based on information on rabies registration for 1881–1980 and zoogeographic data. At that time, 5 rabies enzootic regions were identified, and the most probable directions of further exportation of infection suggested. At first, a review of published data on human and animal rabies cases for the period of 1985–2019 was undertaken (including reference publications). Data on cases of rabies among humans and animals were selected for which geographical coordinates could be determined. Mapping was performed using GIS (QGIS 3.12.0 software and “Natural Earth” and “OpenStreetMap” electronic maps). Comparison of maps for different time periods demonstrated that rabies incidence was recorded mainly within the previously identified risk areas. However, the occurrence of human disease in different regions did not always correspond to the intensity of epizootics and the predicted risk. Next, in an attempt to correct the prognosis of the spatiotemporal rabies spread, we reviewed publications that incorporated virus genetic data along with GIS technology and modeling application. The distribution of the three major rabies virus lineages (“steppe”, “Arctiс-like”, “Arctic”) corresponded to the regions that were previously identified. The spread of fox rabies (the “steppe” rabies virus lineage) in the north-east direction was described. In several instances, rabies outbreaks in southern Siberia and Far East were associated with cross-border movement of the virus from Kazakhstan, Mongolia and China. Data on the speed of the epizootic waves, pathways, and natural barriers for virus spread are discussed. The correction of the forecast for rabies virus circulation and spread is important for the development of control strategies in the region, including oral vaccination of wildlife virus reservoirs.